Simplify. Assume q is greater than or equal to zero. 12q10

Answers

Answer 1
Answer:

Answer:

12q the power of 10

Step-by-step explanation:


Related Questions

Solve: 2a-3b=52a−3b=5a+b=10
What is 6:12 in simplest form?A.2B.21C. 12D. 12.6
The lengths of the bases of the right trapezoid are 9 cm and 18 cm. The length of a longer leg is 15 cm. Find the area of the trapezoid.
Find the value of x in the triangle below.x = ?
6^2+17+12 help me plz.

If g(x)=x squared+2 find g(3)

Answers

Answer:

11

Step-by-step explanation:

x^2+2

(3)^2+2

9+2=11

Reduce 15 1/4 +1 1/2 +3/20 to lowest term.

Answers

15 (1)/(4) +1 (1)/(2) + (3)/(20) =15 (5)/(20) +1 (10)/(20) + (3)/(20)=16 (18)/(20) =16 (9)/(10) =16.9
15  1/4  + 1  1/2   + 3/20

= 61/4 + 1.5 + 0.15

= 15.25 + 1.65

= 16.90
Thus, the answer is 16.90

What is the collection of numbers that includes the natural numbers, together with their negatives and zero?

Answers

we know that
An integer is a whole number (not a fractional number) that can be positive, negative, or zero.
so
the answer is
the collection of numbers that includes the natural numbers, together with their negatives and zero are the integers

Choose the best estimate for the weight of a strawberry A 1 ounce B 8 ounces

Answers

Answer:1 ounce

Step-by-step explanation:

Given the function f ( x ) = − 1 x + 3 x 4 , f(x)=− x 1 ​ + 4 3 x ​ ​ , find f ′ ( 4 ) . f ′ (4). Express your answer as a single fraction in simplest form.

Answers

Step-by-step explanation:

The question is not well written. Let us say the function given as expressed as;

f(x) = -1/x + 3/x⁴

f'(x) means we are to differentiate the function with respect to x;

Given f(x) = axⁿ

f'(x) = naxⁿ⁻¹

f(x) = -x⁻¹ + 3x⁻⁴

Applying the differentiation formula we will have;

f'(x) = -1(-x⁻²)+(-4)3x⁻⁴⁻¹

f'(x) = x⁻²-12x⁻⁵

Express as a fraction

f'(x) = 1/x²-12/x⁵

To get f'(4), we will have to substitute x = 4 into the resulting expression

f'(4) = 1/4²-12/4(5)

f'(4) = 1/16-12/20

f'(4) = 1/16-3/5

Find the LCM

f'(4) = (5-48)/80

f'(4) = -43/80

Note that the function used was assumed but the same method can be employed to any other functions.

Factor 3d^2 - d - 24

Answers

Using the AC method for factoring.....

you should get the answer of...

(3d+8)(d-3)